2015
DOI: 10.1186/s40529-015-0084-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of yam dioscorin interventions on improvements of the metabolic syndrome in high-fat diet-induced obese rats

Abstract: BackgroundThe metabolic syndrome (MS) is termed a cluster of multiple metabolic risk criteria which is positively correlated with cardiovascular disease and type 2 diabetes mellitus (DM). Yam dioscorins have been reported to exhibit biological activities, however, little is known their preventive effects on the MS. Therefore, a high-fat (HF) diet was used to induce Wistar rat obesity and then yam dioscorin (50 mg/kg, dio50) was intervened daily concurrent HF diet (HF diet + dio50) for five weeks to check the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 48 publications
(73 reference statements)
0
38
0
Order By: Relevance
“…All the included studies measured glucose and, although these were measured via a variety of methods (FBG/GTT), they all showed that treatment with either yam or its extract led to significant improvements in glucose tolerance compared to the controls (Table 2). FBG was reported in all studies except Wu et al (2018) and Shih et al (2015), while GTT was measured in five of the ten studies (Xu et al 2020;Wu et al 2018;Shih et al 2015;Kim et al 2012;Hsu et al 2007). Dioscin, dioscorin, DA-9801, DA-9802, Diosgenin and CYP improved FBG (P<0.05), while dioscin, dioscorin, DA-9802 were shown to improve GTT from 30 minutes to 120 minutes after oral or intraperitoneal glucose load (P<0.05).…”
Section: Fbg/gttmentioning
confidence: 94%
See 2 more Smart Citations
“…All the included studies measured glucose and, although these were measured via a variety of methods (FBG/GTT), they all showed that treatment with either yam or its extract led to significant improvements in glucose tolerance compared to the controls (Table 2). FBG was reported in all studies except Wu et al (2018) and Shih et al (2015), while GTT was measured in five of the ten studies (Xu et al 2020;Wu et al 2018;Shih et al 2015;Kim et al 2012;Hsu et al 2007). Dioscin, dioscorin, DA-9801, DA-9802, Diosgenin and CYP improved FBG (P<0.05), while dioscin, dioscorin, DA-9802 were shown to improve GTT from 30 minutes to 120 minutes after oral or intraperitoneal glucose load (P<0.05).…”
Section: Fbg/gttmentioning
confidence: 94%
“…In the rodent model T2DM was induced by consuming high fat diet (HFD) in rats or mice, the KK-A y mice, which spontaneously exhibit T2DM and the db/db mice, a genetic model of T2DM were fed HFD, while the OLETF mice fed normal diet; one study, Hsu et al (2007) fed the rodent model rats with high fructose diet to induce hyperglycaemia. The studies utilised a variety of Dioscorea species although two studies (Li et al 2019;Shih et al 2015) did not mention the yam species. A variety of yam extracts were used in nine of the studies; these included components, Dioscin (Xu et al 2020;Li et al 2019), Dioscorin (Wu et al 2018;Shih et al 2015), Diosgenin (Hashidume et al 2018) and DA-9802 (Moon et al 2014;Kim et al 2012) and Dioscorea esculenta powder (Sato et al 2017); while one study used raw material of Dioscorea Oppesita, (a synonym of two species of yam Discorea polystachya and Dscorea oppositifolioa) (Hsu et al 2007).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…121 The protein hydrolysates from whey, barbel, and yam can reduce the DPP-4 activity in enzymatic measurements. 122125 Through partition by molecular sieve, the highest inhibition peptide sequences of DPP-4 such as Ala-Pro, Leu-Pro-Val-Pro-Gln, Trp-Ser-Gly, and Phe-Ser-Asp have been found. 126128 Nevertheless, these results from in vitro enzymatic assays cannot guarantee a promising future since physiological regulation of DPP-4 is far more complicated than bench-top experiments.…”
Section: Methods For Screening Novel Dpp-4 Inhibitorsmentioning
confidence: 99%
“…The metabolic syndrome is a term for cluster of multiple metabolic risk criteria which is positively correlated with type 2 diabetes mellitus. Shanyao dioscorin interventions exhibit improved metabolic syndrome activities in obese rats, and peptic hydrolysates of Shanyao dioscorin in vitro exhibit DPP IV inhibitory activities (93).…”
Section: Saponins and Flavonesmentioning
confidence: 99%